2022
DOI: 10.2147/cmar.s370397
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Prediction and in vivo Verification Identify SLC7A5 as Immune Infiltration Related Biomarker in Breast Cancer

Abstract: Purpose Solute carrier family 7, member 5 (SLC7A5) is reportedly a key gene in various tumors. However, the relationship between SLC7A5 and immune cell infiltration in breast cancer remains elusive. In this study, we investigated the expression levels and clinical value of SLC7A5 using the R package in breast cancer through the TCGA database. Methods Public transcript data and clinical information of patients were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 271 Another bioinformatics analysis for breast cancer reached a similar conclusion. 272 In addition, BCAT isoenzymes may serve as markers of tumor TME status. In non-malignant T cells, such as activated CD4 + T cells and CTL cells, BCAT c accounts for 50% of the total BCAT expression level, whereas this proportion is upregulated to 60% in T-cell lymphomas.…”
Section: Amino Acid Metabolism In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
See 1 more Smart Citation
“… 271 Another bioinformatics analysis for breast cancer reached a similar conclusion. 272 In addition, BCAT isoenzymes may serve as markers of tumor TME status. In non-malignant T cells, such as activated CD4 + T cells and CTL cells, BCAT c accounts for 50% of the total BCAT expression level, whereas this proportion is upregulated to 60% in T-cell lymphomas.…”
Section: Amino Acid Metabolism In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Subsets with different preferences for BCAA metabolism have also been found in breast cancer, and further studies are needed to determine whether this is due to differences in tumor cells or the involvement of other cells in the microenvironment. 55,59 BCAA metabolism is equally important for the function of proinflammatory CD4 + and CD8 + T cells and immunosuppressive regulatory Treg cells, 41,[265][266][267][268][269][270][271][272] which plays key role in metabolic diseases, liver and kidney diseases. 10,11,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]345,346 Currently, drugs targeting BCAA uptakedependent amino acid transporter LAT1 metabolic enzymes BCAT and BCKDK are in trials.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…61 A recent study showed that SLC7A5 was an immune infiltration-related biomarker and breast cancer patients with high SLC7A5 expression were insensitive to paclitaxel and doxorubicin and had poor prognoses. 62…”
Section: Slc7a5mentioning
confidence: 99%
“…Furthermore, SLC7A5 expression is positively associated with tumor size, histological grade, tumor infiltrating lymphocytes (TILs), and programmed death ligand 1 (PD‐L1) while negatively associated with ER and progesterone receptor (PR) in breast cancer 61 . A recent study showed that SLC7A5 was an immune infiltration‐related biomarker and breast cancer patients with high SLC7A5 expression were insensitive to paclitaxel and doxorubicin and had poor prognoses 62 …”
Section: Amino Acid Transporters In Breast Cancermentioning
confidence: 99%
“…High cellular leucine concentration activates the mTOR pathway and promotes cell proliferation [ 20 ]. SLC7A5 is known to be highly expressed in many cancers [ 21 , 22 ]. In KRAS-mutant colorectal cancer cells, SLC7A5 maintained intracellular amino acid level and activated mTOR pathway, which finally supported cell proliferation [ 23 ]; in small cell lung cancer, increased SLC7A5 promoted cell growth [ 24 ].…”
Section: Introductionmentioning
confidence: 99%